1995
DOI: 10.1080/00218469508028158
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Response of Adhesive Joints to Water Absorption

Abstract: Dielectric measurements have been used to infer the average moisture content of aluminum adhesive joints bonded with three commercial epoxy adhesives. Measurements were made on both aluminum-adhesivealuminum joints and aluminum-adhesive specimens in order to assess the influence of moisture diffusion gradients. Similar experiments were also performed with foil electrodes embedded in the bondline. For average water concentrations less than approximately 2%, there existed a linear relationship between the permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A similar study of aluminium adhesively bonded joints using three dierent commercial epoxy resin systems has been published [20]. Using embedded electrodes it was observed that, for an average water content of less than 2 per cent, a linear relationship exists between the permittivity and the total water content.…”
Section: Study Of Ageing In Adhesively Bonded Structuresmentioning
confidence: 85%
“…A similar study of aluminium adhesively bonded joints using three dierent commercial epoxy resin systems has been published [20]. Using embedded electrodes it was observed that, for an average water content of less than 2 per cent, a linear relationship exists between the permittivity and the total water content.…”
Section: Study Of Ageing In Adhesively Bonded Structuresmentioning
confidence: 85%
“…The effect of absorbed moisture on the molecular interactions and relaxation dynamics in polymer networks is an interesting, fundamentally important and incompletely understood problem. The work presented herein addresses this issue by examining a glassy thermoset network exposed to moisture with the combined use of broadband dielectric relaxation spectroscopy (DRS), Fourier transform infrared spectroscopy (FTIR), and molecular simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al [14] demonstrated that it is possible to monitor the cure of an adhesive using dielectrometry with steel adherends as the two electrodes. Nairn et al [15] showed that it was possible to obtain the dielectric response of an adhesive between two aluminum adherends and determine the moisture level in the adhesive. This could be done using Downloaded by [University of Cincinnati Libraries] at 05:47 03 January 2015 the adherends as electrodes or by embedding an electrode in the center of the adhesive.…”
Section: Introductionmentioning
confidence: 99%